THE INFLUENCE OF THE TEACHER’S WORK DISCIPLINE AND MOTIVATION ON STUDENTS’ LEARNING ACHIEVEMENT AT MODEL ISLAMIC STATE SENIOR HIGH SCHOOL (MAN MODEL) BANDA ACEH - Nelliraharti Nelliraharti (JOURNAL OF EDUCATION SCIENCE, 2015)
The teacher’s work discipline and motivation is the factor that influences students’ learning achievement. This research aimed to investigate whether those factors have any influences or not towards students’ achievement at MAN MODEL Banda Aceh. This research employed descriptive method with quantitative approach. Data were collected with scaled questionnaire and documentation which were analyzed with statistic analysis. The population of the research is the teacher of MAN MODEL Banda Aceh consisting of 61 people. The result of the research showed that (1) the influence of the teacher’s work discipline on the students’ learning achievement was in strong category (0.618) whereas contributions of variable X1 on variable Y was 38.1 percent and the rest of it, 61.9 percent, was determined by other variables. The influencing indicator were purpose and ability, exemplary leadership, fringe benefits, fairness, inherent supervisory, punitive sanctions, and assertiveness and human relation.; (2) the influence of work motivation of the teacher on students’ learning achievement was in strong category (0.499) as well, whereas the contribution of variable X2 on variable Y was 24.9 percent and the rest of it, 75.1 percent, was determined by other variables. The influencing indicators were: internal indicator namely responsibility, carrying out duties, having purposes, there was feedback; external indicators were daily necessities of life, to earn praise, to get incentive, to get attention from friends and superior; (3) the simultaneous influence of X1 and X2 on Y was in strong category (0.696), meanwhile the contribution of X1 and X2 simultaneously on Y was 48.4 percent and the rest of it, 51.6 percent, was determined by other variables.Keywords: Teacher’s Work Discipline, Motivation, and Learning Achievement